ANALISIS PENGGUNAAN APLIKASI WHATSAPP DALAM MENINGKATKAN EFEKTIVITAS KOMUNIKASI INTERPERSONAL PADA HUBUNGAN ASMARA JARAK JAUH : (Studi Kasus Pada Mahasiswa Fakultas Ilmu Sosial Universitas Negeri Jakarta) - Putriana, Muria; Sari, Wina Puspita; Sulistyarini, Dian; Selvyana, Anggun; Sabila, Artati Putri; Tsabitahadi, Edina; Ghania, Fanisa Azwa; Sari, Lulu Kartika Yunita (DIALEKTIKA KOMUNIKA: Jurnal Kajian Komunikasi dan Pembangunan Daerah, 2024)
ABSTRACT   In the dynamics of romantic relationships, a phenomenon that attracts attention is the long-distance relationship (LDR), where both partners are in geographically distant locations. Research by the Center for Long Distance Relationship Research found that 2.9% of couples in the US are in LDRs due to education, work efforts, research, and military deployment. In the age of technology, LDRs are increasingly common among students, including at the Faculty of Social Sciences at Universitas Negeri Jakarta (UNJ). This study examines the use of WhatsApp in improving the effectiveness of interpersonal communication in long-distance romantic relationships among UNJ students. Using qualitative methods, five students who actively use WhatsApp as a communication medium in LDR were observed and interviewed. The results showed that WhatsApp features such as chat, voice call, video call, voice note, share location, and emoticons facilitate communication and contribute significantly to maintaining intimacy and relationship quality. A variety of communication patterns were found, including balanced, monopolized, and imbalanced communication patterns. Overall, WhatsApp proved effective in overcoming barriers to long-distance relationships, providing emotional support, and maintaining intimacy and trust among student couples. This study suggests couples choose the right communication medium and highlights the importance of further research to explore alternative communication mediums in LDR. Keywords: WhatsApp, interpersonal communication, long distance relationships ABSTRAK  Dalam dinamika hubungan asmara, fenomena yang menarik perhatian adalah hubungan jarak jauh atau Long Distance Relationship (LDR), di mana kedua pasangan berada di lokasi geografis yang berjauhan. Penelitian Pusat Penelitian Hubungan Jarak Jauh menemukan bahwa 2,9% pasangan di AS menjalani LDR karena pendidikan, upaya kerja, penelitian, dan penempatan militer. Di era teknologi, LDR semakin umum di kalangan mahasiswa, termasuk di Fakultas Ilmu Sosial Universitas Negeri Jakarta (UNJ). Penelitian ini meneliti penggunaan WhatsApp dalam meningkatkan efektivitas komunikasi interpersonal pada hubungan asmara jarak jauh mahasiswa UNJ. Dengan metode kualitatif, lima mahasiswa yang aktif menggunakan WhatsApp sebagai media komunikasi dalam LDR diobservasi dan diwawancarai. Hasil penelitian menunjukkan bahwa fitur WhatsApp seperti chat, panggilan suara, video call, voice note, share location, dan emoticon, mempermudah komunikasi dan memberikan kontribusi signifikan dalam menjaga keintiman dan kualitas hubungan. Variasi pola komunikasi ditemukan, termasuk pola komunikasi seimbang, monopoli, dan ketidakseimbangan. Secara keseluruhan, WhatsApp terbukti efektif dalam mengatasi rintangan hubungan jarak jauh, memberikan dukungan emosional, dan menjaga keintiman serta kepercayaan di antara pasangan mahasiswa. Penelitian ini menyarankan pasangan memilih media komunikasi yang tepat dan pentingnya penelitian lebih lanjut untuk mengeksplorasi media komunikasi alternatif dalam LDR. Kata Kunci: WhatsApp, Komunikasi Interpersonal, Hubungan Jarak Jauh